Olefin copolymer elastomer and preparation method thereof
Through the quaternary copolymer of ethylene, propylene, cycloolefin and norbornene containing double bonds outside the ring, the shortcomings of existing optical polymer materials in terms of elasticity, flexibility and transparency are solved, and high light transmittance and high light transmittance are prepared. Refractive index olefin copolymer elastomer, suitable for a variety of high-end optical applications and reduces raw material costs.
Patent Information
- Application Number
- CN202411085704.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2024-12-13
AI Technical Summary
The existing optical polymer materials have shortcomings in taking into account elasticity, flexibility, high transparency and high refractive index, which limits their application in the field of high-end optical.
Through the quaternary random copolymer of ethylene, propylene, cycloolefin and norbornene containing double bonds with ring external ring, the copolymerization reaction is carried out using a vanadium-based catalyst to prepare an olefin copolymer elastomer with high light transmittance and high refractive index. .
The olefin copolymer elastomer with high light transmittance and high refractive index has excellent mechanical properties and elasticity. It is suitable for packaging, protective masks, packaging, optical lenses and other fields, reducing raw material costs.
Smart Images

Figure CN119119342A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-performance polymers, and in particular relates to an olefin copolymer elastomer and a preparation method thereof. Background Art
[0002] Optical materials are materials with optical properties and functions. Among them, optical polymer materials have the advantages of shock resistance, light weight, low price and easy molding. They are widely used in optical lenses, instruments, optoelectronic digital and telecommunication products, pharmaceutical packaging and other fields. Common optical polymer materials are mostly optical plastics, including polycarbonate, polymethyl methacrylate, ethylene and cycloolefin copolymer resin (COC), cycloolefin polymer (COP), etc., but optical plastics are hard, brittle, and have poor elasticity and flexibility. See: Handbook of Plastic Optics, Chemical Industry Press, 2013. For ethylene-cycloolefin copolymer resins, in order to achieve excellent transparency and refractive index (transmittance: ~91.0%, refractive index: ~1.53), the molar content of cycloolefins (such as norbornene and dicyclopentadiene) in commercial COC copolymers is usually higher than 40% (for example, when the norbornene content is 38%, the refractive index of the ethylene-norbornene copolymer is 1.52). The high cycloolefin structural unit content causes the glass transition temperature of COC to be higher than 80°C, the elasticity and flexibility are poor, and the elongation at break is The rate is less than 10%; a triblock copolymer of polynorbornene-b-random polypropylene-b-polynorbornene is formed by reacting propylene with a high content of norbornene, which is beneficial to improving the toughness of the material; a ternary random copolymer is prepared by copolymerizing ethylene, propylene and norbornene catalyzed by a constrained geometry catalyst (CGC) metallocene catalyst. When the norbornene content is 50%, its glass transition temperature can reach above 150°C, and its thermal properties are similar to those of ethylene / norbornene copolymers, but its optical properties and physical and mechanical properties have not been reported. See: Ethylene–norbornene copolymersethylene–norbornene copolymers. Encyclopedia of Polymer Science and Technology, p489-497, John Wiley & Sons, Inc.; US20080221275 A1; Macromolecules, 2006, 39, 1913-1919; Journal of Polymer Science, Part A: Polymer Chemistry 2015,53,685-691; ACS Macro Letters,2019,8,299-303.
[0003] Elastomers are polymer materials that deform significantly under weak stress and can recover to a state close to their original state and size after stress relaxation. See: Zhao Xutao, Liu Dahua, Handbook of Synthetic Rubber Industry, Chemical Industry Press, 2006. Olefins are common chemical raw materials and important monomers for producing polymers. Polyolefin elastomers prepared by polymerization of olefins such as ethylene, propylene, 1-butene, 1-hexene and 1-octene as monomers include random copolymers of ethylene and α-olefins (1-butene, 1-hexene or 1-octene) (POE), propylene-based thermoplastic elastomers, ethylene-propylene rubber, etc. POE has excellent transparency, and its light transmittance can reach more than 89%, but its refractive index is low (1.43-1.49). See: Journal of Thermal Analysis and Calorimetry, 2020, 140, 2259-2265; Polymer Data Handbook, Oxford University Press, Inc., 1999. The lower the refractive index, the thicker the material needs to be, which reduces transparency and limits its application in high-end optics.
[0004] EPDM is an elastomer made of ethylene, propylene and non-conjugated olefins. It can be cross-linked by vulcanization, has excellent aging resistance, good electrical insulation, impact elasticity, etc., and is widely used. However, the poor transparency of EPDM limits its application in fields with high transparency requirements such as packaging and protective masks. In order to improve the optical properties of EPDM, processing aids are added during the processing of ordinary EPDM to prepare optically transparent cross-linked EPDM with a transparency greater than 80% and a turbidity less than 10%. The transparency of this type of cross-linked EPDM is not high enough and the turbidity is high. This material can only be used as an alternative material for preparing highly transparent flexible gas mask goggles, see: Rubber Translation Series, 1992, 1, 23-26. However, there is no relevant report on the direct introduction of cycloolefin structural units into the EPDM molecular chain to prepare a quaternary copolymer elastomer with excellent optical properties.
[0005] In summary, the EPDM rubber in the prior art has poor transparency and cannot be used in optical materials; cycloolefin polymers (COC and COP) are thermoplastics and do not have the properties of elasticity, flexibility, high transparency and high refractive index of polymers; polyolefin elastomers (POE) have high transparency but low refractive index, which limits their application in high-end optical materials. Therefore, it is urgent to prepare an olefin copolymer elastomer that has elasticity, flexibility, high transparency and high refractive index. Summary of the invention
[0006] In order to solve the problems of the prior art, the present invention provides an olefin copolymer elastomer and a preparation method thereof. The olefin copolymer elastomer comprises a random copolymer of structural units such as ethylene, propylene, cycloolefin and norbornene containing double bonds outside the ring, and has the characteristics of elasticity, flexibility, high light transmittance and high refractive index.
[0007] In order to achieve the above object, the first aspect of the present invention provides an olefin copolymer elastomer, wherein the olefin copolymer elastomer contains ethylene structural units, propylene structural units, structural units derived from cycloolefins, and structural units derived from norbornene containing an exocyclic double bond;
[0008] The cycloolefin is selected from at least one of the compounds shown in Formula 1; the norbornene containing an exocyclic double bond is selected from at least one of the compounds shown in Formula 2 and Formula 3;
[0009]
[0010] In Formula 1, a is an integer of 0-10, preferably an integer of 0-5, and more preferably an integer of 0-3; R 1 -R 12 Each independently selected from hydrogen, C1-C 20 Alkyl or C4-C 20 The cycloalkyl group is preferably hydrogen or C1-C 10 An alkyl group, more preferably a hydrogen or C1-C6 alkyl group;
[0011] In Formula 2 and Formula 3, b is an integer of 0-10, preferably an integer of 0-5, and more preferably an integer of 0-3; R 13 -R 19 are independently hydrogen or C1-C 20 is preferably hydrogen or C1-C 10 More preferably, it is hydrogen or a C1-C6 alkyl group.
[0012] The second aspect of the present invention provides a method for preparing the olefin copolymer elastomer, comprising the following steps:
[0013] Under the action of a catalyst, ethylene, propylene, cycloolefin and norbornene containing an exocyclic double bond are copolymerized to prepare the olefin copolymer elastomer.
[0014] The effects of the present invention are as follows:
[0015] (1) A tetraolefin copolymer elastomer with adjustable copolymer composition and molecular weight can be prepared by copolymerizing ethylene, propylene, cycloolefin and norbornene containing an exocyclic double bond.
[0016] (2) The catalyst and polymerization method of the present invention make cycloolefins more easily copolymerized than propylene, and the amount of propylene fed can be reduced by introducing cycloolefins.
[0017] (3) The olefin copolymer elastomer prepared by the present invention has high light transmittance and high refractive index. The light transmittance can reach 91.1%, and the refractive index can reach 1.531.
[0018] (4) The method of the present invention can significantly reduce the haze of olefin copolymer elastomer films.
[0019] (5) Compared with the COC product having a molar content of norbornene structural units of 48.5%, the molar content of norbornene structural units required for the olefin copolymer elastomer prepared by the method of the present invention to achieve a transmittance and a refractive index similar to those of COC is only 27.0%, thereby significantly reducing the amount of norbornene monomer used and reducing the cost of raw materials.
[0020] (6) The olefin copolymer elastomer prepared by the method of the present invention has excellent elasticity and mechanical properties, with a breaking strength of up to 30.3 MPa and an elongation at break of up to 570%. In addition, the prepared copolymer side groups also contain double bonds, which can be further used to prepare a strong polymer network through chemical cross-linking.
[0021] (7) The olefin copolymer elastomer prepared by the method of the present invention has high light transmittance, high refractive index, excellent mechanical properties and elasticity, and can be used in packaging, protective masks, packaging, optical lenses, instruments and meters, optoelectronic digital and telecommunication products, biomedicine and other fields that have high requirements for transparency and elasticity.
[0022] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0024] Figure 1 The transparency and flexibility of the quaternary random copolymer film obtained in Example 10 of the present invention are shown.
[0025] Figure 2 The stress-strain curve of the cross-linked tetra-random copolymer film obtained in Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0026] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0027] In order to achieve the above object, the first aspect of the present invention provides an olefin copolymer elastomer, wherein the olefin copolymer elastomer contains ethylene structural units, propylene structural units, structural units derived from cycloolefins, and structural units derived from norbornene containing an exocyclic double bond;
[0028] The cycloolefin is selected from at least one of the compounds shown in Formula 1; the norbornene containing an exocyclic double bond is selected from at least one of the compounds shown in Formula 2 and Formula 3;
[0029]
[0030]
[0031] In Formula 1, a is an integer of 0-10, preferably an integer of 0-5, and more preferably an integer of 0-3; R 1 -R 12 Each independently selected from hydrogen, C1-C 20 Alkyl or C4-C 20 The cycloalkyl group is preferably hydrogen or C1-C 10 An alkyl group, more preferably a hydrogen or C1-C6 alkyl group;
[0032] In Formula 2 and Formula 3, b is an integer of 0-10, preferably an integer of 0-5, and more preferably an integer of 0-3; R 13 -R 19 are independently hydrogen or C1-C 20 is preferably hydrogen or C1-C 10 More preferably, it is hydrogen or a C1-C6 alkyl group.
[0033] In the present invention, the structural unit derived from cycloolefin is selected from at least one of the structural units shown in Formula 4;
[0034]
[0035] The structural unit derived from norbornene containing an exocyclic double bond is selected from at least one of the structural units represented by Formula 5 and Formula 6;
[0036]
[0037] According to the present invention, preferably, based on the molar number of all structural units in the olefin copolymer elastomer, the molar content of ethylene structural units is 35% to 80%, preferably 45% to 75%, and more preferably 50% to 70%; the molar content of propylene structural units is 6% to 40%, preferably 7% to 35%, and more preferably 8% to 30%; the molar content of structural units derived from cycloolefins is 5% to 37%, preferably 7% to 35%, and more preferably 9% to 30%; the molar content of structural units derived from norbornene containing an exocyclic double bond is 0.02% to 5.0%, preferably 0.05% to 4.0%, and more preferably 0.1% to 3.0%.
[0038] According to the present invention, preferably, the weight average molecular weight of the olefin copolymer elastomer is 10 to 2000 kg / mol, preferably 50 to 1000 kg / mol, more preferably 100 to 800 kg / mol.
[0039] According to the present invention, preferably, the olefin copolymer elastomer has a light transmittance of not less than 89%, a refractive index of not less than 1.495, a haze of not more than 5%, and an elongation at break of more than 220%.
[0040] The second aspect of the present invention provides a method for preparing the olefin copolymer elastomer, comprising the following steps:
[0041] Under the action of a catalyst, ethylene, propylene, cycloolefin and norbornene containing an exocyclic double bond are copolymerized to prepare the olefin copolymer elastomer.
[0042] According to the present invention, preferably, the catalyst is a vanadium-based catalyst.
[0043] According to the present invention, preferably, the vanadium-based catalyst comprises the following components:
[0044] Component A: main catalyst, the main catalyst is selected from the general formula VOCl2OR 1 and VOCl(OR 1 )(OR 2 ) shown in at least one of the vanadium-containing compounds, wherein R 1 and R 2 The same or different, each independently selected from C1 to C 10 Alkyl, C1~C 10 haloalkyl, C3~C 10 Cycloalkyl, C3~C 10 Halogenated cycloalkyl or C6~C 25 Preferably, R 1 and R 2Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, 2,2-dichloro-1-ethyl, 1,1-dichloro-2-propyl, 1,1-dichloro-2-methyl-2-propyl, 3,3-dichloro-1-propyl, 2,2-dichloro-1-propyl, 1,1-dichloro-2-butyl, 3,3-dichloro-1-butyl, 2,2-dichloro-1-butyl, 1,1-dichloro R is 1,1,1-trichloro-2-butyl, 1,1,1-trichloro-2-butyl, 1,1,1-trichloro-2-butyl, 2,2-dichloro-1-pentyl, 2,2-dichloro-1-hexyl, 2,2,2-trichloro-1-ethyl, 3,3,3-trichloro-1-propyl, 1,1,1-trichloro-2-propyl, 1,1,1-trichloro-2-methyl-2-propyl, 1,1,1-trichloro-2-butyl, or 1,1,1-trichloro-2-methyl-2-butyl. 2 It can also be selected from p-methylphenoxy, 2-methylphenoxy, 2-ethylphenoxy, 4-ethylphenoxy, 2-isopropylphenoxy, 2-tert-butylphenoxy, 2-sec-butylphenoxy, 2,4-dimethylphenoxy, 2,6-dimethylphenoxy, 2,3,4-trimethylphenoxy, 2,3,5-trimethylphenoxy, 2,3,6-trimethylphenoxy, 2,4,6-trimethylphenoxy, 2,4-diethylphenoxy, 2,6-diethylphenoxy, 2,4,6 - at least one of triethylphenoxy, 2,3-di-tert-butylphenoxy, 2,4-di-tert-butylphenoxy, 2,5-di-tert-butylphenoxy, 2,6-di-tert-butylphenoxy, 2,3,4-tri-tert-butylphenoxy, 2,3,5-tri-tert-butylphenoxy, 2,3,6-tri-tert-butylphenoxy, 2,4,6-tri-tert-butylphenoxy, 2,6-di-tert-butyl-4-methylphenoxy, 4-tert-pentylphenoxy, 3-pentadecylphenoxy and 4-tert-octylphenoxy.
[0045] Component B: a cocatalyst, wherein the cocatalyst is an organoaluminum compound; preferably, the organoaluminum compound is selected from at least one of alkylaluminum, alkylaluminum halide and alkylaluminoxane; the alkylaluminum and the alkylaluminum halide are selected from the general formula R m AlX 3-m At least one of the compounds shown, wherein R is C1~C 10 Alkyl, C3~C 10 Cycloalkyl, C7~C 10 Arylalkyl and C6~C 10, X is a halogen, preferably Cl or Br, and m is 1, 1.5, 2 or 3; more preferably, the alkylaluminum is selected from at least one of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-n-pentylaluminum, tri-n-hexylaluminum and tricyclohexylaluminum; the alkylaluminum halide is selected from at least one of dimethylaluminum chloride, diethylaluminum chloride, di-n-butylaluminum chloride, diisobutylaluminum chloride, methylaluminum dichloride, ethylaluminum dichloride, n-butylaluminum dichloride, isobutylaluminum dichloride, sesquimethylaluminum chloride, sesquiethylaluminum chloride, sesqui-n-butylaluminum chloride and sesqui-isobutylaluminum chloride; the alkylaluminoxane is selected from at least one of methylaluminoxane, ethylaluminumoxane and isobutylaluminumoxane; commercial alkylaluminoxanes usually also contain a certain amount (e.g., ~20%) of alkylaluminum.
[0046] Component C: activator; Component C is an activator commonly used in the art that can oxidize low-valent vanadium to high-valent vanadium. Preferably, Component C is a C1-C 20 hydrocarbons or C2~C 20 The addition of component C is beneficial to improving the copolymerization performance of the catalyst. Therefore, in order to improve the copolymerization efficiency of α-olefins and cycloolefins, component C needs to be added.
[0047] According to the present invention, preferably, the molar ratio of component B calculated as Al element to component A calculated as V element is 7 to 120:1, preferably 10 to 100:1, and more preferably 15 to 80:1; the molar ratio of component C to component A calculated as V element is 0 to 10:1, preferably 0 to 8:1, and more preferably 0 to 7:1; and further preferably 0 to 6:1.
[0048] In the present invention, the amount of component B is related to factors such as the impurity content, the amount of the primary catalyst, the amount of monomer, the molecular weight and molecular weight distribution of the polymerized product in the system. Usually, increasing the amount of the cocatalyst in the polymerization system within a certain range can improve the polymerization activity. Too little cocatalyst produces a small number of active centers, low catalytic activity, and low monomer polymerization conversion. However, too much cocatalyst can cause the primary catalyst to be excessively reduced on the one hand, affecting the monomer conversion, and on the other hand, cause chain transfer, and the molecular weight of the polymer decreases. In addition, too much cocatalyst can also cause the catalyst cost to increase.
[0049] According to the present invention, if the monomer concentration in the polymerization system is too high, the system viscosity will be too large, affecting the production process. If the monomer concentration is too low, the amount of solvent used will increase, increasing the cost. In the present invention, a suitable monomer concentration is necessary. Preferably, the monomer concentration is 10 to 180 g / L, preferably 20 to 150 g / L, and more preferably 30 to 120 g / L.
[0050] According to the present invention, the polymerization reaction can be adiabatic polymerization or isothermal polymerization. The starting temperature of the polymerization reaction is -60 to 80°C, preferably -50 to 70°C, and more preferably -40 to 60°C.
[0051] In the present invention, the monomer conversion rate and polymer yield will increase as the reaction time is prolonged. The reaction rate is relatively fast at the beginning of the polymerization reaction. As the reaction time is prolonged, part of the catalyst is deactivated and the reaction rate slows down. Therefore, the polymerization reaction time is generally selected to be 1 min to 2 h, preferably 2 min to 1.5 h, and more preferably 2.5 min to 1.2 h.
[0052] In the present invention, the polymerization reaction pressure is related to the polymerization temperature. The higher the temperature, the greater the pressure. In addition, increasing the pressure is conducive to the gas monomer dissolving in the solution for polymerization reaction, but too high a pressure will have high pressure resistance requirements for the polymerization reactor. Therefore, the polymerization pressure is generally selected to be 0.01 to 3 MPa, preferably 0.05 to 2 MPa, and more preferably 0.1 to 1 MPa.
[0053] The polymerization method of the present invention includes bulk polymerization, solution polymerization or slurry polymerization, which can be a batch process or a continuous process. The monomers can be fed once, in batches or continuously.
[0054] In the present invention, when solution polymerization is adopted, the solvent used can be selected from the group consisting of C3 to C 10 Saturated alkanes, C3~C 10 Cycloalkanes or C6~C 10 At least one of the aromatic hydrocarbons is preferably selected from at least one of n-butane, n-pentane, cyclopentane, n-hexane, cyclohexane, methylcyclopentane, methylcyclohexane, n-heptane, n-octane, isooctane, n-nonane, n-decane, toluene and xylene. The choice of solvent is related to the polymerization process conditions, polymer molecular weight and molecular weight distribution. Generally, in order to prepare high molecular weight polymers, a solvent that is not prone to chain transfer can be selected; in order to prepare low molecular weight polymers, a solvent that is prone to chain transfer can be selected.
[0055] The tetrapolymer 1 H NMR test, the contents of ethylene, propylene, cycloolefin and cycloolefin structural unit containing exocyclic double bonds in the copolymer were calculated according to the integrated areas of characteristic peaks.
[0056] The number average molecular weight (M) of the polymer was measured by high temperature GPC at 150 °C using trichlorobenzene as solvent. n ), weight average molecular weight (M w ) and molecular weight distribution index (M w / M n ).
[0057] The transmittance and haze of polymer films were measured using the Shenguang WGT-2S transmittance / haze tester. The transmittance and haze test values of polymer films are related to their thickness. The greater the thickness, the lower the transmittance test value and the higher the haze test value.
[0058] The refractive index of polymers was measured using a WAY-3S digital Abbe refractometer.
[0059] Mechanical properties test: Samples were prepared and tested according to the national standard (GB / T 528-2009). The polymer film was cut with a 4×75mm dumbbell cutter and tested using an INSTRON3345 universal tensile machine. The film was stretched at a speed of 500mm / min until it broke, and the tensile strength and elongation at break of the polymer were measured.
[0060] Example 1
[0061] In a reactor, 0.2 g of norbornene (NB), 0.06 mL of vinyl norbornene (VNB), 3.2 mmol of sesquiethylaluminum chloride and 0.04 mmol of trichloro-tert-butyl-o-tert-butyl-p-methylphenylvanadium chloride were added to 18 mL of n-hexane and 12 mL of cyclohexane in an ethylene / propylene mixed gas (molar ratio of 1:2). After the polymerization reaction was carried out at -30°C for 10 min, a 5 wt% ethanol solution of hydrochloric acid was added to terminate the polymerization reaction. The polymer in the solution was precipitated with ethanol, and the precipitated polymer solid was dried to constant weight in a vacuum oven at 40°C to obtain 0.67 g of dry E / P / NB / VNB tetrapolymer, wherein: the molar content of ethylene structural units (C E ) is 66.5%, and the molar content of propylene structural units (C P ) is 23.0%, and the molar content of NB structural units (C NB ) is 9.9%, and the molar content of VNB structural units (C VNB ) is 0.6%.
[0062] The weight average molecular weight (M w ) is 711 kg / mol, and the molecular weight distribution (M w / M n ) is 2.11, and the glass transition temperature (T g ) is -28.7℃.
[0063] The tetrapolymer is made into a film with a thickness of 0.158 mm, good flexibility, a light transmittance of 91.1%, a refractive index of 1.495 and a haze of 5%.
[0064] Compared with the ethylene-propylene binary random copolymer with similar ethylene structural unit content in Comparative Example 1, the transmittance of the quaternary random copolymer described in this embodiment is increased by 5.6%, the refractive index is increased by 0.018, and the haze is reduced by 51%.
[0065] With ethylene, propylene and ENB terpolymer (Comparative Example 5, C E Compared with the quaternary random copolymer described in this embodiment, the transmittance is increased by 4.3%, the refractive index is increased by 0.013, and the haze is reduced by 31%.
[0066] Compared with the terpolymer of ethylene, propylene and NB (Comparative Example 8), the transmittance of the quaternary random copolymer described in this embodiment is increased by 2.0%, the refractive index is increased by 0.002, and the haze is reduced by 4%.
[0067] Compared with the ternary copolymer of ethylene, propylene and VNB (Comparative Example 9), the transmittance of the quaternary random copolymer described in this embodiment is increased by 1.2%, the refractive index is increased by 0.024, and the haze is reduced by 28%.
[0068] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer described in this embodiment is increased by 0.015 and 0.007, respectively.
[0069] The tetrapolymer was made into a sample strip with a thickness of 0.193 mm for tensile testing. The results showed that the elastic modulus was 3.1 MPa, the breaking strength was 4.0 MPa, and the breaking elongation was 569%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0070] Example 2
[0071] The polymerization method is similar to that of Example 1, except that 0.4 g of NB is added to obtain 0.46 g of E / P / NB / VNB tetrapolymer, wherein: C E 62.5%, C P 20.3%, C NB 16.6%, C VNB The M w is 461kg / mol, M w / M n is 1.97, T g It is -2.5℃.
[0072] The tetrapolymer is made into a film with a thickness of 0.141 mm, and the light transmittance, refractive index and haze are 91.0%, 1.507 and 3%.
[0073] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 2, the transmittance of the quaternary random copolymer described in this embodiment is increased by 3.8%, the refractive index is increased by 0.029, and the haze is reduced by 22%.
[0074] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5, similar to CE), the transmittance of the quaternary random copolymer described in this embodiment is increased by 4.2%, the refractive index is increased by 0.025, and the haze is reduced by 33%.
[0075] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer described in this embodiment is increased by 0.027 and 0.019, respectively.
[0076] The tetrapolymer was made into a sample strip with a thickness of 0.174 mm for tensile testing. The results showed that the elastic modulus was 11.5 MPa, the breaking strength was 15.3 MPa, and the breaking elongation was 531%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0077] 500 mg of the obtained tetrapolymer was dissolved in 20 mL of cyclohexane, and 24 mg of diisopropylbenzene peroxide was added. After uniform mixing, the solvent was volatilized and dried to obtain a sample. The sample was hot-pressed at 80°C and 20 MPa for 30 min, then heated to 165°C and hot-pressed for 10 min for cross-linking. After cooling, a film with a thickness of 0.196 mm was obtained, with a light transmittance of 90.0%, a refractive index of 1.514, and a haze of 9%.
[0078] The cross-linked samples were made into strips for tensile testing. The results showed that the elastic modulus was 14.3 MPa, the breaking strength was 25.7 MPa, and the breaking elongation was 328% (as shown in Figure 2). Figure 2 The elastic modulus and breaking strength of the cross-linked material are significantly improved.
[0079] Example 3
[0080] The polymerization method is similar to that of Example 1, except that 0.6 g of NB is added to obtain 0.49 g of E / P / NB / VNB tetrapolymer, wherein: C E is 61.1%, C P 20.5%, C NB 18.0%, C VNB The M of the tetrapolymer is 0.4%. w is 496 kg / mol, M w / M n is 1.87, T g It is 5.4℃.
[0081] The tetrapolymer is prepared into a film with a thickness of 0.146 mm, a light transmittance of 90.2%, a refractive index of 1.510 and a haze of 5%.
[0082] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 2, the transmittance of the quaternary random copolymer described in this embodiment is increased by 3.0%, the refractive index is increased by 0.032, and the haze is reduced by 20%.
[0083] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 3.4%, the refractive index is increased by 0.028, and the haze is reduced by 31%.
[0084] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer described in this embodiment is increased by 0.030 and 0.022, respectively.
[0085] The polymer was made into strips with a thickness of 0.193 mm for tensile testing. The results showed that the elastic modulus was 20.2 MPa, the breaking strength could reach 30.0 MPa, and the breaking elongation was 413%, indicating excellent mechanical properties, elasticity and toughness.
[0086] Example 4
[0087] The polymerization method is similar to that of Example 1, except that 0.8 g of NB is added to obtain 0.50 g of E / P / NB / VNB tetrapolymer, wherein: C E 58.1%, C P 20.7%, C NB 20.8%, C VNB The M of the tetrapolymer is 0.4%. w is 500 kg / mol, M w / M n is 1.84, T g It is 15.1℃.
[0088] The tetrapolymer was made into a film with a thickness of 0.130 mm, with a light transmittance of 90.9%, a refractive index of 1.519, and a haze of 4%. Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 2, the tetrapolymer of the present invention has a light transmittance increased by 3.7%, a refractive index increased by 0.041, and a haze reduced by 21%.
[0089] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 4.1%, the refractive index is increased by 0.037, and the haze is reduced by 32%.
[0090] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer is increased by 0.037 and 0.029, respectively.
[0091] The tetrapolymer was made into a sample strip with a thickness of 0.184 mm for tensile testing. The results showed that the elastic modulus was 15.6 MPa, the breaking strength was 30.2 MPa, and the breaking elongation was 375%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0092] Example 5
[0093] The polymerization method is similar to that of Example 1, except that the molar ratio of ethylene to propylene is 1:1, and 1.0 g of NB is added. 0.74 g of E / P / NB / VNB tetrapolymer is obtained, wherein: C E is 62.3%, C P 16.5%, C NB 20.8%, C VNB The M of the tetrapolymer is 0.4%. w is 493 kg / mol, M w / M n is 1.84, T g It is 21.4℃.
[0094] The tetrapolymer is made into a film with a thickness of 0.167 mm, a light transmittance of 90.2%, a refractive index of 1.518 and a haze of 5%.
[0095] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 2, the transmittance of the quaternary random copolymer of the present invention is increased by 3.0%, the refractive index is increased by 0.040, and the haze is reduced by 20%.
[0096] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 3.4%, the refractive index is increased by 0.036, and the haze is reduced by 31%.
[0097] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer is increased by 0.038 and 0.030, respectively.
[0098] The tetrapolymer was made into a sample strip with a thickness of 0.167 mm for tensile testing. The results showed that the elastic modulus was 224.7 MPa, the breaking strength was 36.0 MPa, and the breaking elongation was 354%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0099] Example 6
[0100] The polymerization method is similar to that of Example 1, except that 1.0 g NB and 0.02 mL VNB are added to obtain 1.09 g E / P / NB / VNB tetrapolymer, wherein: C E 57.8%, C P 23.4%, C NB 18.6%, C VNB The M of the tetrapolymer is 0.2%. w is 621kg / mol, M w / M n is 1.77, T g It is 20.4℃.
[0101] The tetrapolymer was made into a film with a thickness of 0.131 mm, with a light transmittance of 90.9%, a refractive index of 1.513, and a haze of 4%. Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 3, the tetrapolymer random copolymer in this embodiment has a light transmittance increased by 2.4%, a refractive index increased by 0.035, and a haze reduced by 11%.
[0102] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 4.1%, the refractive index is increased by 0.036, and the haze is reduced by 31%.
[0103] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer is increased by 0.033 and 0.025, respectively.
[0104] The tetrapolymer was made into a sample strip with a thickness of 0.177 mm for tensile testing. The results showed that the elastic modulus was 16.6 MPa, the breaking strength was 31.1 MPa, and the breaking elongation was 385%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0105] Example 7
[0106] The polymerization method was similar to that of Example 6, except that 0.12 mL of ENB was added. 1.17 g of E / P / NB / ENB tetrapolymer was obtained, wherein: E 53.1%, C P25.2%, C NB The molar content of ENB structural units (C ENB ) is 1.4%. The M w is 603 kg / mol, M w / M n is 1.81, T g It is 23.7℃.
[0107] The tetrapolymer is made into a film with a thickness of 0.159 mm, a light transmittance of 89.4%, a refractive index of 1.518 and a haze of 3%.
[0108] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 3, the transmittance of the quaternary random copolymer described in this embodiment is increased by 0.9%, the refractive index is increased by 0.040, and the haze is reduced by 12%.
[0109] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 2.6%, the refractive index is increased by 0.036, and the haze is reduced by 33%.
[0110] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer is increased by 0.038 and 0.030, respectively.
[0111] The tetrapolymer was made into a sample strip with a thickness of 0.159 mm for tensile testing. The results showed that the elastic modulus was 126.3 MPa, the breaking strength was 25.9 MPa, and the breaking elongation was 325%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0112] Example 8
[0113] The polymerization method was similar to that of Example 7, except that 0.18 mL of ENB was added. 1.20 g of E / P / NB / ENB tetrapolymer was obtained, wherein: E 52.0%, C P 23.6%, C NB 22.3%, C ENB The M of the tetrapolymer is 2.1%. w is 616 kg / mol, M w / M n is 1.77, T g It is 22.6℃.
[0114] The tetrapolymer is made into a film with a thickness of 0.148 mm, a light transmittance of 89.7%, a refractive index of 1.516, and a haze of 4%.
[0115] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 3, the transmittance of the quaternary random copolymer described in this embodiment is increased by 1.2%, the refractive index is increased by 0.041, and the haze is reduced by 11%.
[0116] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 2.9%, the refractive index is increased by 0.034, and the haze is reduced by 32%.
[0117] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer is increased by 0.036 and 0.028, respectively.
[0118] The tetrapolymer was made into a sample strip with a thickness of 0.148 mm for tensile testing. The results showed that the elastic modulus was 6.8 MPa, the breaking strength was 22.3 MPa, and the breaking elongation was 483%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0119] Example 9
[0120] The polymerization method is similar to that of Example 5, except that the molar ratio of ethylene to propylene is 8:1. 0.75 g of E / P / NB / VNB tetrapolymer is obtained, wherein: C E 68.5%, C P 8.2%, C NB 22.9%, C VNB The copolymer M w is 607 kg / mol, M w / M n is 1.78, T g It is 29.6℃.
[0121] The tetrapolymer is made into a film with a thickness of 0.176 mm, a light transmittance of 90.3%, a refractive index of 1.521 and a haze of 5%.
[0122] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 1, the transmittance of the quaternary random copolymer described in this embodiment is increased by 4.8%, the refractive index is increased by 0.044, and the haze is reduced by 52%.
[0123] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 3.5%, the refractive index is increased by 0.039, and the haze is reduced by 31%.
[0124] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer described in this embodiment is increased by 0.041 and 0.033, respectively.
[0125] The tetrapolymer was made into a sample strip with a thickness of 0.176 mm for tensile testing. The results showed that the elastic modulus was 456 MPa, the breaking strength was 33.8 MPa, and the breaking elongation was 278%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0126] Compared with the films prepared from commercial polyolefin elastomers in Comparative Examples 5, 6 and 7, the polymer films of the present invention have a high refractive index.
[0127] Example 10
[0128] The polymerization method is similar to that of Example 9, except that: the solvent used is 30 mL of cyclohexane, the ethylene / propylene molar ratio used is 4:1, 0.64 g of NB, 0.1 mL of VNB, and 1.2 mmol of sesquiethylaluminum chloride are added, and copolymerization is carried out at 13°C. 0.63 g of copolymer is obtained, which is a tetrapolymer of E / P / NB / VNB, wherein: C E is 62.4%, C P 9.2%, C NB 27.0%, C VNB The copolymer M w is 191 kg / mol, M w / M n is 1.91, T g It is 43.3℃.
[0129] The tetrapolymer is made into a film with a thickness of 0.160 mm, a light transmittance of 90.9%, a refractive index of 1.531 and a haze of 3%.
[0130] Compared with the binary ethylene-propylene random copolymer with similar ethylene structural unit content in Comparative Example 2, the transmittance of the quaternary random copolymer described in this embodiment is increased by 3.7%, the refractive index is increased by 0.053, and the haze is reduced by 22%.
[0131] Compared with the terpolymer of ethylene, propylene and ENB (Comparative Example 5), the transmittance of the quaternary random copolymer described in this embodiment is increased by 4.1%, the refractive index is increased by 0.049, and the haze is reduced by 33%.
[0132] Compared with the commercial POE shown in Comparative Examples 6 and 7, the refractive index of the quaternary random copolymer described in this embodiment is increased by 0.051 and 0.043, respectively.
[0133] Compared with the commercial COC membrane of Comparative Example 4, the quaternary random copolymer membrane described in this embodiment has good flexibility.
[0134] The tetrapolymer was made into a sample strip with a thickness of 0.160 mm for tensile testing. The results showed that the elastic modulus was 14.7 MPa, the breaking strength was 21.6 MPa, and the breaking elongation was 224%, and the tetrapolymer had excellent mechanical properties, elasticity and toughness.
[0135] Compared with the COC product (CNB=48.5%) in Comparative Example 4, the tetrapolymer described in this embodiment has similar light transmittance and refractive index, and has stretchable and bendable properties, which are incomparable to the COC product. In particular, the CNB in the tetrapolymer described in this embodiment is only 27.0%, which is significantly lower than the CNB value in the COC product, thereby greatly reducing the amount of norbornene used and reducing the production cost.
[0136] Compared with the COC product in Comparative Example 4, the elongation at break of the tetrapolymer described in this embodiment is increased by 66 times.
[0137] Comparative Example 1
[0138] A mixture of ethylene and propylene in a molar ratio of 1:3 was introduced into a reactor containing 50 mL of n-hexane, and then 2.25 mmol of sesquiethylaluminum chloride and 0.015 mmol of a vanadium catalyst were added in sequence, and the polymerization reaction was carried out at -45°C for 10 min. The post-treatment method was the same as in Example 1. 1.1 g of an E / P binary copolymer was obtained, wherein: C E is 66.1%, C P It is 33.9%.
[0139] The binary copolymer was made into a film with a thickness of 0.182 mm using the same film-making method as in the example, with a light transmittance of 85.5%, a refractive index of 1.477, and a haze of 57%.
[0140] Comparative Example 2
[0141] A mixture of ethylene and propylene in a molar ratio of 1:2 was introduced into a reactor containing 50 mL of n-hexane, and then 1.5 mmol of sesquiethylaluminum chloride and 0.02 mmol of a vanadium catalyst were added in sequence, and the polymerization reaction was carried out at -35°C for 10 min. The post-treatment method was the same as in Example 1. 1.23 g of an E / P binary copolymer was obtained, wherein: C E is 60.7%, C P It is 39.3%.
[0142] The binary copolymer was made into a film with a thickness of 0.146 mm using the same film-making method as in the example, with a light transmittance of 87.2%, a refractive index of 1.478, and a haze of 25%.
[0143] Comparative Example 3
[0144] 50 mL of n-hexane solution was added to the reactor, and 0.5 MPa of propylene gas was introduced, followed by ethylene gas to 0.7 MPa, and then 0.4 mmol of sesquiethylaluminum chloride and 0.005 mmol of vanadium catalyst were added in sequence. The polymerization reaction was carried out at 10°C for 20 min. The post-treatment method was the same as in Example 1. 1.2 g of E / P binary copolymer was obtained, wherein: C E 55.5%, C P It is 44.5%.
[0145] The binary copolymer was made into a film with a thickness of 0.150 mm using the same film-making method as in the example, with a light transmittance of 88.2%, a refractive index of 1.475, and a haze of 15%.
[0146] Comparative Example 4
[0147] Using the same film-making method as in Example 1, a commercial COC sample (C E 51.5%, C NB The film was made into a 0.141 mm thick film with a light transmittance of 90.5%, a haze of 5.3%, and a refractive index of 1.530. The film was very brittle and easy to break, with a tensile strength of 39.4 MPa and an elongation at break of 3.3%.
[0148] Comparative Example 5
[0149] The same film-making method as in the first embodiment was used to prepare a commercial product, E / P / ENB terpolymer (C E is 65.1%, C P 33.1%, C ENB 1.8%) was made into a film with a thickness of 0.171 mm, a transmittance of 86.8%, a refractive index of 1.482, and a haze of 36%.
[0150] Comparative Example 6
[0151] The same film-making method as in Example 1 was used to prepare the commercial POE sample (C E The molar content of 1-butene structural unit (C B ) is 18.2%) and has a thickness of 0.137 mm. Its transmittance is 92.8%, the refractive index is 1.480, and the haze is 5.0%.
[0152] Comparative Example 7
[0153] The same film-making method as in the example was used to prepare the commercial POE sample (C E The molar content of 1-octene structural unit (C O ) is 10.9%) A film with a thickness of 0.138 mm was prepared by the same molding method as in the embodiment, and its transmittance was 92.6%, the refractive index was 1.488, and the haze was 1.0%.
[0154] Comparative Example 8
[0155] The polymerization method is similar to that of Example 1, except that 0.2 g of NB is added, and no vinyl norbornene (VNB) is added, to obtain 0.95 g of E / P / NB terpolymer, wherein: C E 57.1%, C P 34.5%, C NB The terpolymer was made into a film with a thickness of 0.154 mm, and its light transmittance was 89.1%, the refractive index was 1.493, and the haze was 9%.
[0156] Comparative Example 9
[0157] The polymerization method is similar to that of Example 1, except that NB is not added, 0.06 mL of vinyl norbornene (VNB) is added, and 0.78 g of E / P / VNB terpolymer is obtained, wherein: C E is 66.1%, C P 33.0%, C VNB The terpolymer is made into a film with a thickness of 0.173 mm, and its light transmittance is 89.9%, the refractive index is 1.471, and the haze is 33%.
[0158] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. An olefin copolymer elastomer, It is characterized in that The olefin copolymer elastomer contains ethylene structural units, propylene structural units, structural units derived from cycloolefins, and structural units derived from norbornene containing an exocyclic double bond; The cycloolefin is selected from at least one of the compounds shown in Formula 1; the norbornene containing an exocyclic double bond is selected from at least one of the compounds shown in Formula 2 and Formula 3; In Formula 1, a is an integer of 0-10, preferably an integer of 0-5, and more preferably an integer of 0-3; R 1 -R 12 are each independently selected from hydrogen, C 1 -C 20 Alkyl or C 4 -C 20 The cycloalkyl group is preferably hydrogen or C 1 -C 10 Alkyl, more preferably hydrogen or C 1 -C 6 The alkyl group; In Formula 2 and Formula 3, b is an integer of 0-10, preferably an integer of 0-5, and more preferably an integer of 0-3; R 13 -R 19 are independently hydrogen or C 1 -C 20 is preferably hydrogen or C 1 -C 10 Alkyl, more preferably hydrogen or C 1 -C 6 of alkyl.
2. The olefin copolymer elastomer according to claim 1, in, Based on the molar number of all structural units in the olefin copolymer elastomer, the molar content of ethylene structural units is 35% to 80%, preferably 45% to 75%, and more preferably 50% to 70%; the molar content of propylene structural units is 6% to 40%, preferably 7% to 35%, and more preferably 8% to 30%; the molar content of structural units derived from cycloolefins is 5% to 37%, preferably 7% to 35%, and more preferably 9% to 30%; the molar content of structural units derived from norbornene containing an exocyclic double bond is 0.02% to 5.0%, preferably 0.05% to 4.0%, and more preferably 0.1% to 3.0%.
3. The olefin copolymer elastomer according to claim 1, in, The weight average molecular weight of the olefin copolymer elastomer is 10 to 2000 kg / mol, preferably 50 to 1000 kg / mol, and more preferably 100 to 800 kg / mol.
4. The olefin copolymer elastomer according to claim 1, in, The olefin copolymer elastomer has a light transmittance of not less than 89%, a refractive index of not less than 1.495, a haze of not more than 5%, and an elongation at break of more than 220%.
5. A method for preparing an olefin copolymer elastomer according to any one of claims 1 to 4, It is characterized in that The steps include: Under the action of catalyst, ethylene, C 3 -C 4 The olefin copolymer elastomer is prepared by copolymerizing an α-olefin, a cycloolefin and a norbornene containing an exocyclic double bond.
6. The preparation method according to claim 5, in, The catalyst is a vanadium-based catalyst.
7. The preparation method according to claim 6, in, The vanadium-based catalyst comprises the following components: Component A: main catalyst, the main catalyst is selected from the general formula VOCl 2 OR 1 and VOCl(OR 1 )(OR 2 ) shown in at least one of the vanadium-containing compounds, wherein R 1 and R 2 The same or different, each independently selected from C 1 ~C 10 Alkyl, C 1 ~C 10 The halogenated alkyl, C 3 ~C 10 Cycloalkyl, C 3 ~C 10 halocycloalkyl or C 6 ~C 25 Preferably, R 1 and R 2 Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, 2,2-dichloro-1-ethyl, 1,1-dichloro-2-propyl, 1,1-dichloro-2-methyl-2-propyl, 3,3-dichloro-1-propyl, 2,2-dichloro-1-propyl, 1,1-dichloro-2-butyl, 3,3-dichloro-1-butyl, 2,2-dichloro-1-butyl, 1,1-dichloro-2-pentyl, 2,2-dichloro -1-pentyl, 1,1-dichloro-2-hexyl, 2,2-dichloro-1-hexyl, 2,2,2-trichloro-1-ethyl, 3,3,3-trichloro-1-propyl, 1,1,1-trichloro-2-propyl, 1,1,1-trichloro-2-methyl-2-propyl, 1,1,1-trichloro-2-butyl, 1,1,1-trichloro-2-methyl-2-butyl, p-methylphenoxy, 2-methylphenoxy, 2-ethylphenoxy, 4- Ethylphenoxy, 2-isopropylphenoxy, 2-tert-butylphenoxy, 2-sec-butylphenoxy, 2,4-dimethylphenoxy, 2,6-dimethylphenoxy, 2,3,4-trimethylphenoxy, 2,3,5-trimethylphenoxy, 2,3,6-trimethylphenoxy, 2,4,6-trimethylphenoxy, 2,4-diethylphenoxy, 2,6-diethylphenoxy, 2,4,6-triethylphenoxy, 2,3-ditert-butylphenoxy At least one of butylphenoxy, 2,4-di-tert-butylphenoxy, 2,5-di-tert-butylphenoxy, 2,6-di-tert-butylphenoxy, 2,3,4-tri-tert-butylphenoxy, 2,3,5-tri-tert-butylphenoxy, 2,3,6-tri-tert-butylphenoxy, 2,4,6-tri-tert-butylphenoxy, 2,6-di-tert-butyl-4-methylphenoxy, 4-tert-pentylphenoxy, 3-pentadecylphenoxy and 4-tert-octylphenoxy; Component B: a cocatalyst, wherein the cocatalyst is an organoaluminum compound; preferably, the organoaluminum compound is selected from at least one of alkylaluminum, alkylaluminum halide and alkylaluminoxane; the alkylaluminum and the alkylaluminum halide are selected from the general formula R m AlX 3-m At least one of the compounds shown, wherein R is C 1 ~C 10 Alkyl, C 3 ~C 10 Cycloalkyl, C 7 ~C 10 Aralkyl and C 6 ~C 10 , X is a halogen, preferably Cl or Br, and m is 1, 1.5, 2 or 3; more preferably, the alkylaluminum is selected from at least one of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-n-pentylaluminum, tri-n-hexylaluminum and tricyclohexylaluminum, the alkylaluminum halide is selected from at least one of dimethylaluminum chloride, diethylaluminum chloride, di-n-butylaluminum chloride, diisobutylaluminum chloride, methylaluminum dichloride, ethylaluminum dichloride, n-butylaluminum dichloride, isobutylaluminum dichloride, sesquimethylaluminum chloride, sesquiethylaluminum chloride, sesqui-n-butylaluminum chloride and sesqui-isobutylaluminum chloride; the alkylaluminoxane is selected from at least one of methylaluminoxane, ethylaluminumoxane and isobutylaluminumoxane; Component C: activator; the component C is C containing 2 to 5 chlorine atoms 1 ~C 20 hydrocarbons or C 2 ~C 20 of esters.
8. The preparation method according to claim 7, in, The molar ratio of component B calculated as Al element to component A calculated as V element is 7 to 120:1, preferably 10 to 100:1, and more preferably 15 to 80:1; The molar ratio of component C to component A calculated as V element is 0 to 10:1, preferably 0 to 8:1, more preferably 0 to 7:1; further preferably 0 to 6:
1.
9. The preparation method according to claim 5, in, The copolymerization reaction includes: a monomer concentration of 10 to 180 g / L, preferably 20 to 150 g / L, and more preferably 30 to 120 g / L; a starting temperature of -60 to 80°C, preferably -50 to 70°C, and more preferably -40 to 60°C; a reaction time of 1 min to 2 h, preferably 2 min to 1.5 h, and more preferably 2.5 min to 1.2 h; and a polymerization pressure of 0.01 to 3 MPa, preferably 0.05 to 2 MPa, and more preferably 0.1 to 1 MPa.
10. The preparation method according to claim 5, in, The copolymerization reaction adopts bulk polymerization, solution polymerization or slurry polymerization; Preferably, the copolymerization reaction is carried out by solution polymerization, and the solvent used is selected from C 3 ~C 10 Saturated alkanes, C 3 ~C 10 Cycloalkanes or C 6 ~C 10 At least one of the aromatic hydrocarbons is preferably selected from at least one of n-butane, n-pentane, cyclopentane, n-hexane, cyclohexane, methylcyclopentane, methylcyclohexane, n-heptane, n-octane, isooctane, n-nonane, n-decane, toluene and xylene.
